The psychological impact of COVID-19 pandemic on healthcare workers - Tong, Fei; Zhang, Lemeng; Huang, Liping; Yang, Hongxia; Wen, Minni; Jiang, Ling; Zou, Ran; Liu, Feng; Peng, Wanglian; Huang, Xufen; Yang, Desong; Yang, Hui; et al. (Frontiers in Public Health, 2022)
Background As unprecedented and prolonged crisis, healthcare workers (HCWs) are at high risk of developing psychological disorders. We investigated the psychological impact of COVID-19 pandemic on HCWs. Methods This cross-sectional study randomly recruited 439 HCWs in Hunan Cancer Hospital via a web-based sampling method from June 1st 2021 to March 31st 2022. Anxiety and depression levels were measured using Hospital Anxiety and Depression Scale (HADS). The Post Traumatic Stress Disorder (PTSD) Checklist for DSM-5 (PCL-5) was used to assess the presence and severity of PTSD. Fear was measured by modified scale of SARS. Data were collected based on these questionnaires. Differences in fear, anxiety, depression and PTSD among HCWs with different clinical characteristics were analyzed using a multivariate analysis of variance. The Cronbach's alpha scores in our samples were calculated to evaluate the internal consistency of HADS, fear scale and PCL-5. Results The prevalence of anxiety, depression, and PTSD in HCWs was 15.7, 9.6, and 12.8%, respectively. Females and nurses were with higher fear level (P < 0.05) and higher PTSD levels (P < 0.05). Further analysis of female HCWs revealed that PTSD levels in the 35–59 years-old age group were higher than that in other groups; while married female HCWs were with increased fear than single HCWs. The internal consistency was good, with Cronbach's α = 0.88, 0.80 and 0.84 for HADS, fear scale, and PCL, respectively. Conclusion Gender, marital status, and age are related to different level of psychological disorders in HCWs. Clinical supportive care should be implemented for specific group of HCWs.